Key Success Factor for Successful ERP Implementation in State Owned Enterprises - Rahayu, Sri; Juliana Dillak, Vaya (International Journal of Engineering and Technology, 2018)
ERP implementation is a way to improve competitive advantage, and ERP is one of the factors that affect the company's performance. However, many studies reveal that many companies trying to implement ERP failed although in the end many were successful. To achieve its success, several key factors to be considered include top management support, effective project management, business process reengineering, hardware and software selection, education and training, and vendor support. This study aims to explore the key of successful implementation of ERP in state-owned enterprises in Bandung, Indonesia. Related to state owned enterprises that have failed and succeeded in the implementation of ERP, the effective management project analysis has a significant influence on the success of system implementation while top management support, business process reengineering, hardware and software selection, education and training and vendor support have no effect on the success of ERP implementation. However all variables studied simultaneously have effects on the success of ERP implementation.Â Â